2014
DOI: 10.1038/srep05463
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides: Minor Lipids Make a Major Impact on Photoreceptor Cell Functions

Abstract: Activation of the phosphoinositide (PI) cycle generates the second messengers that control various aspects of cellular signaling. We have previously shown that two PI cycle enzymes, type II phosphatidylinositol 5-phosphate 4-kinase (PIPK IIα) and phosphoinositide 3-kinase (PI3K), are activated through light stimulation. In our earlier studies, we measured enzyme activities, instead of directly measuring the products, due to lack of sensitive analytical techniques. Cells have very low levels of PIs, compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…DHA is highly abundant in retinal layers and is the major PUFA component (up to 60%) . The major tissue phosphatidyl inositol PI(38:4) m/z 885.5497 was found predominantly confined to the photoreceptor cell layer (inner and outer segments), consistent with the functional role of PIs in rod outer segments, and at lower abundances throughout other tissues types (Figure E). The ganglioside, GM1(38:1) m/z 1572.9090, was detected at low abundance and localised in the inner retinal layers (nerve fibre layer and ganglion cell layer) and optic nerve bundle, consistent with its previous detection in mammalian retinae …”
Section: Resultssupporting
confidence: 60%
“…DHA is highly abundant in retinal layers and is the major PUFA component (up to 60%) . The major tissue phosphatidyl inositol PI(38:4) m/z 885.5497 was found predominantly confined to the photoreceptor cell layer (inner and outer segments), consistent with the functional role of PIs in rod outer segments, and at lower abundances throughout other tissues types (Figure E). The ganglioside, GM1(38:1) m/z 1572.9090, was detected at low abundance and localised in the inner retinal layers (nerve fibre layer and ganglion cell layer) and optic nerve bundle, consistent with its previous detection in mammalian retinae …”
Section: Resultssupporting
confidence: 60%
“…The lipid substrate phosphatidylinositol (PI) serves as a substrate for PI3K to form PI-3-P [24]. PI-3-P antibody was used to stain retinal sections from dark- and light-adapted Nrl −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…This was accomplished by delivering constructs encoding GFP sensors of PI(4,5)P 2 and PI(4)P into mouse rods by in vivo electroporation. Previous studies had reported light-dependent changes in the levels of these phosphoinositides [ 33 ] and their modulatory effects on the phototransduction cascade [ 34 ] and enzymatic activities (also reviewed in [ 16 , 17 , 35 , 36 ]). Therefore, we designed experiments allowing us to assess the presence of phosphoinositides in different subcellular compartments of the rod cells, particularly the light-sensitive outer segment.…”
Section: Resultsmentioning
confidence: 99%